2018
DOI: 10.1038/s41433-018-0141-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in retinal nerve fiber layer thickness measurements in response to a trifocal intraocular lens implantation

Abstract: The IOL implantation produce changes in the RNFL thickness, which are larger in case of a trifocal diffractive IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Similarly to our findings, an increase in macular thickness 22 and RNFL thickness 23,24 were reported after cataract surgery with monofocal and trifocal IOL. Authors proposed several factors to justify those changes, such as inflammation, changes in vitreous body volume, image quality improvement owing to cataract extraction, or variations in repeatability and reproducibility.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly to our findings, an increase in macular thickness 22 and RNFL thickness 23,24 were reported after cataract surgery with monofocal and trifocal IOL. Authors proposed several factors to justify those changes, such as inflammation, changes in vitreous body volume, image quality improvement owing to cataract extraction, or variations in repeatability and reproducibility.…”
Section: Discussionsupporting
confidence: 91%
“…However, our protocol is in line with earlier studies in which just one quality measurement was required in every analysis visit. 23 In addition, it represents a realistic situation in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The implantation of trifocal IOLs is steadily increasing and it is necessary to determine how they might affect OCT measurements. García-Bello et al [ 19 ] found that the implantation of a trifocal diffractive IOL (AT LISA® Tri 839 MP, Zeiss) produced a higher difference in average pRNFL measurements than the implantation of a monofocal IOL (CT ASPHINA 409 M/MP): 7.29 ± 10.51 µ m versus 1.96 ± 2.90 µ m, respectively, p =0.017. However, the results of this study must be taken cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of this study must be taken cautiously. Only 25 eyes were included per group and the trifocal group had a low preoperative average pRNFL with a wide standard deviation: 79.67 ± 15.21 µ m versus 100.35 ± 6.44 µ m for the monofocal group [ 19 ]. Thus, the greater difference found for trifocal lens might have been due to inaccurate preoperative measurements.…”
Section: Discussionmentioning
confidence: 99%
“…García-Bella et al [ 46 ] found an increase in RNFL three months after CCS with multifocal IOLs (96.77 vs. 99.55). To the best of our knowledge, only one study [ 47 ] has compared the effects of monofocal vs. multifocal IOL implantation on the change in OCT measurements. It assessed only one parameter, the RNFL, and found an increase in OCT measurements after CCS in both groups, but its magnitude was greater in the case of multifocal IOL implantation.…”
Section: Discussionmentioning
confidence: 99%